Peranan Masyarakat Adat Serampas dalam Pengendalian Perusakan Hutan di Provinsi Jambi - Ika Dwimaya Roza (Wajah Hukum, 2022)
In Indonesia, there are 50 to 70 million indigenous peoples, and many of them around 50 million people rely on forests for their livelihoods. When compared with the size of the country of Indonesia, customary forest owned by indigenous peoples is only about and only 0.5% of customary land in Indonesia is legally recognized as customary land. The SerampasCommunity in Merangin, Jambi Province received confirmation through local regulation number 8 of 2016 regarding the recognition and protection of the Serampas customary law community. The ratification of this Regional Regulation is in line with the implementation of the decision of the Constitutional Court (MK)-35, regarding customary forests and related laws and regulations. The contents of this Regional Regulation are to declare, acknowledge, and convey protection against the existence and traditional rights of the Serampas customary law community which have been neglected, contained in Article 5 paragraph (2) of Law no. 41 of 1999 regarding the recognition of customary rights. Using this Regional Regulation, as access to empowerment and development there. This type of research in this journal uses normative legal research or literature that includes research on legal principles and research on the legal system. The approach in the preparation of this research uses a legal approach and a conceptual approach. The activities of the land management of the indigenous peoples of Serampas their local and traditional cultures, as well as their spiritual correlation use the forest as the basis for effective and sustainable forest protection, especially in Jambi Province. because indigenous peoples basically make a crucial contribution to achieving the goals of maintaining the world's climate, the balance of forest ecosystems, biological diversity and sustainable development.